The emergency visit-based syndromic surveillance of the Lazio region. Results of the pilot phase (Italian Journal of Public Health, 2009)
Introduction: Syndromic surveillance arose from the need for rapid identification of unexpected clusters of a disease. The emergecy department is considered one of the most sensitive and timely sources of information for syndromic surveillance.Methods: This paper reports the results of the pilot phase (4 months) of an Emergency-based syndromic surveillance system in the Lazio region (5.5 million inhabitants), which aimed to monitor in real time the occurrence of clusters of 13 different syndromes. It collected information online from 34 of the 61 emergency departments in the region. Diagnoses and chief complaints of individual emergency visits were automatically screened daily, the occurrence of clusters were measured comparing the number of visits for the same syndrome with those from the same calendar week from the previous five years; an epidemiology team checks the clusters manually before determining if an alarm should be called.Results: 500.000 ER visits occurred in the study period, and 15.343 fulfilled one of the case criteria. The most frequent syndrome was gastroenterisis (5051 cases), the least frequent was hemorrhagic diarrhoea (2 cases). There were 253 automatically generated alarms and 17 were confirmed manually as suspected outbreaks. In the same period, the infectious disease surveillance identified 55 outbreaks of infectious diseases; only two clusters were reported by both surveillance systems.Conclusions: the predicted increase in workload is one more outbreak to be investigated every four months per local health unit. The next step will be to test protocols for the activation of the public health services following an alarm.
Keywords: Syndromic surveillance; Emergency; Infectious disease reporting; outbreaks